Risk and incidence of endocrine immune related adverse effects under checkpoint inhibitor mono or combination therapy in solid tumors: a meta-analysis of randomized controlled trials [data] - Vardarli, Irfan; Tan, Susanne; Brandenburg, Tim Niclas; Weidemann, Frank; Görges, Rainer; Herrmann, Ken; Führer, Dagmar (Universität, 2023)
Supplemental Materials Abstract Context Few meta-analyses regarding the incidence of endocrine immune related adverse effects (eirAEs) have been published and many trials were published thereafter. Objective To assess the risk and incidence of eirAEs of any grade and grade 3-5 by immune checkpoint inhibitor (ICI) mono or combination-therapy in solid tumors current literature was updated in this comprehensive meta-analysis. Methods An electronic search using PubMed/Medline, Embase and the Cochrane Library was performed. Randomized controlled studies (RCT) assessing eirAEs under ICI-mono or ICI-combination therapy were selected. Stata software version 17 was used for statistical analyses and risk of bias was evaluated by using Review Manager version 5.3. Results 69 RCTs with 80 independent reports, involving 42,886 patients were included in the study. Meta-analysis revealed the following pooled estimates for the risk ratio and the incidence, respectively: for any grade hypothyroidism 7.81 (95% CI, 5.68-10.74, p< 0.0001) and 7.64% (95% CI, 6.23-9.17, p< 0.0001); significantly increased also for hyperthyroidism, hypophysitis/hypopituitarism and adrenal insufficiency; and for insulin-dependent diabetes mellitus 1.52 (95% CI, 1.07-2.18, p= 0.02), and 0.087% (95% CI, 0.019-0.189, p= 0.0006), respectively. Meta-regression showed that combination of ICIs (nivolumab plus ipilimumab and durvalumab plus tremelimumab, respectively) is an independent risk factor for any grade hypophysitis/hypopituitarism, and that ICI agent is an independent factor of risk for adrenal insufficiency, but that cancer type is not an independent risk factor for eirAEs. Conclusion We showed that risk, independent from cancer type, and incidence of eAEs are substantially increased under ICI therapy. Combination of ICIs is increasing the risk for eirAEs, in particular for hypophysitis/hypopituitarism.
Gesehen am 29.11.2023
Keywords: Forschungsdaten; Datenbank